Rancang Bangun Incubator dengan Suhu dan Kelembaban Udara Terkendali untuk Penetasan Telur Ulat Sutera - Dewa Made Subrata; Ahmad Nurman Sajuri; Ade Priyadi; Hotnida CH Siregar (PERTETA, 2013)
AbstractSilkworms were the poikilothermic animals with life cycle strongly affected by environment condition such as temperature, humidity, light and wind. In other the silkworm’s egg hatcheries uniformly at the sameday, it was considered necessary to use the temperature and humidity controllable room (incubation room) according to their optimum hatcheries condition. The incubation room consisted of four actuators i.e: theheater, the cooler, the mist maker, and the water content absorber. All of that actuators were controlled based on the output signal from the sensor (SHT11). In this research the temperature was controlled at the value of 25°C, while the humidity was controlled at the value of 75 %. The experimental result of the incubator machine without silkworm egg shown that the incubator was able to control the temperature at the value of 25°C with maximum 25.4°C. It was also able to control humidity at optimum interval i.e: 73.9 % to 76.1 %. Experimental result with silkworm egg showed that the incubator was able to increase the uniformity of the hatcheries day, even though the hatcheries day was late about two days compared to the conventional method.Key words: incubator, controllable room, hatchery, silkworms egg.AbstrakUlat sutera tergolong hewan poikilotermik yaitu siklus hidupnya sangat dipengaruhi oleh kondisi lingkungan (suhu, kelembaban, cahaya dan angin). Supaya telur ulat sutera menetas secara seragam padahari yang sama, maka perlu digunakan ruang yang suhu dan kelembabannya dapat dikendalikan pada nilai optimum penetasannya. Rancangan ruang inkubasi terdiri dari empat unit aktuator yaitu: pemanas, pendingin, pengkabut dan penyerap uap air. Keempat perangkat tersebut dikendalikan berdasarkan nilai pengukuran yang dihasilkan oleh sensor suhu dan kelembaban jenis SHT11. Pada penelitian ini suhu dikendalikan pada nilai 25°C dan kelembaban pada nilai 75%. Hasil pengujian pada kondisi tanpa telur menunjukkan bahwa incubator mampu mempertahankan suhu pada nilai 25°C dengan suhu maksimum25.4°C demikian juga untuk kelembaban dipertahankan pada selang nilai 73.9 % sampai 76.1 %. Hasil pengujian pada kondisi dengan telur ulat sutera Bombyx mori L. menunjukkan bahwa incubator mampumeningkatkan keseragaman hari penetasan telur namun penetasannya lebih lambat dua hari dibandingkan dengan metoda konvensional.Kata kunci: inkubator, ruang terkendali, penetasan, telur ulat sutera.Diterima: 20 Maret 2013; Disetujui: 02 Juli 2013